Flexural behaviours of steel-UHPC-steel sandwich beams with J-hook connectors. (June 2020) - Yan, Jia-Bao; Hu, Huitao; Wang, Tao
Abstract: This paper firstly developed high performance sandwich composite beams with novel J-hooks and ultra-high performance concrete (UHPC), i.e., steel-UHPC-steel sandwich composite beams with J-hooks (SUSSBJs). Nine full-scale two-point loading tests were then performed on SUSSBJs to study their ultimate strength behaviour. The test results revealed that all SUSSBJs exhibited flexural failure even for SUSSSBJs with short shear span ratio of 2.41 and high spacing of J-hooks of 200 mm due to the high performance UHPC. The test results showed the SUSSBJs exhibited a four-stage working mechanism, which were initial elastic, elastic, nonlinear developing, and hardening stage. The test results also detailed reported and discussed the influences of key parameters on flexural behaviour of SUSSBJs. The flexural bending resistance of SUSSBJs was reduced for small shear span ratios; the spacing of J-hooks did not change the flexural failure mode, but reduces its ultimate strength as well as working mechanism; and all the strength and stiffness indexes increase linearly with the increasing thickness of faceplate . Finally, this paper developed analytical models on stiffness and strengths indexes of SUSSBJs, and the validations against nine test results proved their capabilities on predicting these indexes. Highlights: High performance steel-UHPC-steel sandwich structures with J-hooks (SUSSSJ) are developed Flexural behavior of SUSSSJs are studied through nine four-point bending tests Key parameters influencing structural behaviours of SUSSSJs are revealed Developed theoretical models predict well strength and stiffness of SUSSSJs